2021
DOI: 10.1200/op.20.01062
|View full text |Cite
|
Sign up to set email alerts
|

Care Delivery Impact of the COVID-19 Pandemic on Breast Cancer Care

Abstract: PURPOSE: COVID-19 has altered healthcare delivery. Previous work has focused on patients with cancer and COVID-19, but little has been reported on healthcare system changes among patients without COVID-19. METHODS: We performed a retrospective study of patients with breast cancer (BC) in New York City between February 1, 2020, and April 30, 2020. New patients were included as were patients scheduled to receive intravenous or injectable therapy. Patients with COVID-19 were excluded. Demographic and treatment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 30 publications
4
50
0
Order By: Relevance
“…[ 27 , 28 ] Single-centre studies from the US report that around half of patients on chemotherapy had treatment modifications in February to April 2020. [ 29 , 30 ] A systematic review found evidence of significant delays and disruptions to cancer care worldwide during the COVID-19 pandemic. [31] Apart from New Zealand data, there have been few studies of changes to systemic cancer therapy use in the Western Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 , 28 ] Single-centre studies from the US report that around half of patients on chemotherapy had treatment modifications in February to April 2020. [ 29 , 30 ] A systematic review found evidence of significant delays and disruptions to cancer care worldwide during the COVID-19 pandemic. [31] Apart from New Zealand data, there have been few studies of changes to systemic cancer therapy use in the Western Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has had consequences for cancer care, as a substantial part of cancer diagnoses and treatments worldwide were delayed or disrupted [ 3 , 7 , 18 , 19 ]. During the first month of the pandemic, a study assessing the impact of COVID-19 on breast cancer care in New York reported that 42.6% ( n = 149) of the patients experienced a cancer care delay and/or change [ 20 ]. In Australia, 42% ( n = 683) of cancer patients and survivors experienced disruption to their cancer care or treatment during the early months of the pandemic [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Practice reductions in breast imaging created schedule alterations resulting in delays in screening and treatment, as the focus was shifted to caring for patients with COVID-19. 5 For African American and Hispanic patients who already experience delays in screening and treatment, the pandemic has increased delays. 5 Evidence has shown that these delays resulted in lower rates of cancers detected at screening and larger tumor size compared to pre-pandemic values.…”
Section: Introductionmentioning
confidence: 99%
“… 5 For African American and Hispanic patients who already experience delays in screening and treatment, the pandemic has increased delays. 5 Evidence has shown that these delays resulted in lower rates of cancers detected at screening and larger tumor size compared to pre-pandemic values.…”
Section: Introductionmentioning
confidence: 99%